#KaburAjaDulu: The Influence of National Resilience on Migration Intention Among Indonesian Gen Z - Muhamad Adrian; Qibti Adewiyah Lestari; Nira Mahdiyata; Ahmad Sulaiman (Center for Populatioan and Policy Studies Universitas Gadjah Mada, 2026)
The viral social media phenomenon #KaburAjaDulu reflects high migration intentions among Indonesian Generation Z (aged 19–28) seeking better lives and career opportunities abroad. This phenomenon poses a potential brain drain issue that could impede the realization of the Golden Indonesia 2045 Vision. Therefore, this study addresses a fundamental research question: Does national resilience significantly influence Generation Z's migration intention, and how is this dynamic explained within the Theory of Planned Behavior framework?. In this context, national resilience is conceptualized as a nation's collective capacity to foster stability and optimism in facing adversity, thereby strengthening citizens' trust in their country's future. This research employs a non-experimental quantitative approach with a simple correlational design. The study subjects comprised 365 Generation Z respondents in Indonesia engaged with the trend, selected via accidental sampling. Data were collected using the National Resilience Scale (NR-13) and the Intention to Emigrate Scale. The hypothesis was tested using simple linear regression analysis. The results indicate that national resilience significantly reduces migration intention. This study demonstrates that national resilience is a crucial factor influencing decisions to migrate. Low levels of nationalism, unity, and trust in public institutions tend to increase migration intention. These findings highlight the importance of strengthening national resilience to retain quality human capital in Indonesia.